Les représentations de la non-monogamie consensuelle : perceptions des parents polyamoureux ou en couple ouvert canadiens - Milaine Alarie; Morag Bosom (Genre, Sexualité et Société)
Despite the cultural imperative in Western societies for individuals to practice monogamy, a considerable proportion of individuals report having engaged in consensual non-monogamous (CNM) relationships at some point in their life. To what extent are CNM relationships socially accepted? Through 34 semi-structured interviews conducted with Canadian parents who are polyamorous or in open relationships and their partners, we explore the participants’ representations of consensual non-monogamy, both the way they believe others to be reading them with regard to the way they do intimate relationships and the way they perceive themselves. Results show that parents involved in CNM relationships perceive others to hold negative assumptions about them with regard to their sexuality, the stability of their romantic relationships and the family environment they provide for their children. We also note that being a parent is seen by participants as exacerbating the negative reactions they face, and that gender influences, to some extent, these reactions. Ultimately, this study contributes to a better understanding of social changes related to sexuality and intimate relationships.